2020
DOI: 10.1080/20469047.2020.1805260
|View full text |Cite
|
Sign up to set email alerts
|

Review of Ebola virus disease in children – how far have we come?

Abstract: Ebola virus (EBOV) causes an extremely contagious viral haemorrhagic fever associated with high mortality. While, historically, children have represented a small number of total cases of Ebolavirus disease (EVD), in recent outbreaks up to a quarter of cases have been in children. They pose unique challenges in clinical management and infection prevention and control. In this review of paediatric EVD, the epidemiology of past EVD outbreaks with specific focus on children is discussed, the clinical manifestation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 132 publications
(209 reference statements)
0
9
0
Order By: Relevance
“…Two different species of the Ebola virus were confirmed, namely EBOV-Zaire (EBOV-Z) and EBOV-Sudan (EBOV-S) [ 6 ]. The largest outbreak of EVD so far, from December 2013 to January 2016 resulted in around 28,000 recorded cases, and led to over 11,000 deaths [ 7 ]. A re-emergence of the EVD occurred in Gouécké, Nzérékoré Region, Guinea between 18 January and 13 February 2021.…”
Section: Introductionmentioning
confidence: 99%
“…Two different species of the Ebola virus were confirmed, namely EBOV-Zaire (EBOV-Z) and EBOV-Sudan (EBOV-S) [ 6 ]. The largest outbreak of EVD so far, from December 2013 to January 2016 resulted in around 28,000 recorded cases, and led to over 11,000 deaths [ 7 ]. A re-emergence of the EVD occurred in Gouécké, Nzérékoré Region, Guinea between 18 January and 13 February 2021.…”
Section: Introductionmentioning
confidence: 99%
“…Children are potentially more vulnerable to NI because of their care needs, resulting in frequent contact with HWs or caregivers. High CFRs in children highlight the need for a targeted IPC strategy for this group, including caregivers and families ( Dixit et al., 2020 ). This study also reported high CFRs in adults aged >65 years; however, details on potential comorbidities in this group were unavailable.…”
Section: Discussionmentioning
confidence: 99%
“… 2 Of note, previous retrospective studies looking at children under five years of age have documented lower rates of fever (63–79%), highlighting that children with EVD may not present with fever. 2 In 2015, a WHO report on 7292 patients from the 2014 outbreak, compared the clinical manifestations of three age cohorts (<16, 16–44, and >45) and showed that children under 16 reported fewer symptoms such as abdominal pain, arthralgia, chest pain, headache, and myalgias. 9 This could be related to children's limited ability to self-report symptoms and does not necessarily rule out these manifestations.…”
Section: Introductionmentioning
confidence: 91%
“…The clinical manifestations of EVD in paediatric patients were summarized by Dixit et al 2 Signs and symptoms include fever (63–100%), anorexia (55–99%), weakness (74–98%), diarrhoea (42–80%), vomiting (36–70%), and abdominal pain (35–60%). 2 Of note, previous retrospective studies looking at children under five years of age have documented lower rates of fever (63–79%), highlighting that children with EVD may not present with fever.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation